The Influence of Product, Price, and Promotion on Purchase Decisions of Healthy care Products - ULFA NURUS SAADAH; Bayu Kurniawan; Noni setyorini (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research explores the influence of product, price, and promotion on purchasing decisions of healthy care products among students at Universitas PGRI Semarang. Using an associative method, the study involved 100 respondents selected through incidental sampling. Data were collected via questionnaires and analyzed using descriptive analysis, validity and reliability tests, classical assumption tests, hypothesis testing, and coefficient of determination (R²). The results indicate that product, price, and promotion have a significant positive effect on purchasing decisions. The findings suggest that improving these factors can enhance consumer purchasing decisions, offering valuable insights for businesses in developing effective marketing strategies.